Analisis Kepuasan Pengguna Terhadap Aplikasi Dolan Banyumas Menggunakan Metode End User Computing Satisfaction (EUCS) dan DeLone and McLean - Fadillah, Septiya Nur; Hidayah, Debby Ummul; Saputra, Jeffri Prayitno Bangkit (LPPM Universitas Potensi Utama, 2024)
Technology has an important role in modern life, including in the tourism sector. The Dolan Banyumas application, which was launched by the Banyumas district Youth, Sports, Culture and Tourism Department, is one of the innovations to improve the regional tourism experience. The Dolan Banyumas application was created to make it easier for travelers to find a guide to enjoy the beauty of Banyumas with complete facilities. This research aims to identify problem points experienced by users and propose potential improvements for the application. Apart from that, this research also aims to determine the level of user satisfaction with the Dolan Banyumas application and examine several factors that have an influence on user satisfaction. This research uses the End User Computing Satisfaction (EUCS) and DeLone and McLean methods. The population in this study were users of the Dolan Banyumas application in the Banyumas district, with 82 respondents being the research sample. Data analysis was carried out using PLS-SEM with Microsoft Excel tools for demographic data and SmartPLS for statistical analysis. The research results show that the Dolan Banyumas application has several problem points that need to be improved, such as content, accuracy, format, ease of use, system quality and service quality variables which show a low level of satisfaction. However, the timeliness and information quality variables show a good level of satisfaction. So it can be concluded that the factors that influence user satisfaction with the Dolan Banyumas application use the End User Computing Satisfaction (EUCS) and DeLone and McLean methods, namely information quality and timeliness.